(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The non-linear Volterra integral equations system arises in various fields of science and engineering, posing significant challenges for obtaining exact solutions. In this research, we propose a novel approach to approximate solutions for such systems by employing explicit-implicit methods